Corporate Social Marketing, Drunken Tourism and Sustainability: The Case of Meliá Hotels International in Magaluf, Spain. - Cruz-Morato, Marco Antonio; Rodríguez-Sánchez, Carla; Sánchez, Carolina (Springer Nature, 2023)
This case study uses a corporate social marketing perspective to present an example of tourism sustainability promotion. It focuses on the case of Magaluf (Spain), a tourist destination known for its history of drunken tourism and balconing. This case study examines the actions of Meliá Hotels International, in particular the #TheNewMagaluf campaign. The campaign content was analysed. The analysis focused on the message, tone, purpose, graphic design, media and target audience. The impact of the online social marketing campaigns (mainly in terms of online traffic through views on YouTube and social media impact) was also analysed using Hashtagify. These social marketing actions, among others, have enhanced tourism sustainability in Magaluf and have created benefits for both companies and residents. They provide an opportunity to reposition the image of Magaluf.
https://www.springernature.com/gp/open-science/policies/book-policies
Keywords: Turismo - Aspectos ambientales; Responsabilidad social de la empresa; Corporate social marketing; Sustainable tourism; Social media; Drunken tourism; Magaluf